Kinetic effects in cadmium antimonide crystals before and after gamma-irradiation - Fedosov, S. A.; Zakharchuk, D. A.; Кoval Y. V.; Yashchynskiy, L. V.; Urban, O. A. (Physics and Chemistry of Solid State, 2020)
The influence of large doses of 60Co gamma-quanta on the electrical properties of cadmium antimonide crystals with different electrical conductivity has been investigated. It is revealed that radiation defects of both donor and acceptor types are introduced into the lattice of the material with gamma-irradiation. Their influence depends on the level of doping and the type of conductivity of the starting material. The effectiveness of removal of carriers is a consequence of the involvement of impurity atoms in the formation of corresponding radiation defects with deep energy levels.